Transactional and in‐store display data of a large supermarket for data‐driven decision‐making. (19th October 2020) - Zhao, Lin; Li, Lefei; Shen, Zuo‐Jun Max
Abstract: This article describes daily and monthly transactional and in‐store display data of a large supermarket from January to October in 2019 associated with 28 757 stock‐keeping units (SKUs) in 5 categories and 41 subcategories. The database contains five parts, including information about each SKU, in‐store display, daily sales, inventory, and replenishment. We also propose some research questions related to assortment planning, pricing, inventory management, and customer behavior. Researchers are welcome to develop data‐driven models or other innovative methods to address these questions or other practical problems using this database.